Improving Students’ Reading Comprehension in Narrative Text through Picture-Series at the Eight Grade Student of SMP Wahid Hasyim Dinoyo Malang - Siti Nur Holila (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
The research aimed to find out whether there was improvement in students’ reading comprehension in narrative text after being taught by using picture series in the eight the grade of SMP Wahid Hasyim Dinoyo Malang. This is a Classroom Action Research (CAR) which was conducted in one cycle. Each cycle consisted of four steps: planning, action, observation and reflection. The data were collected from field notes and interview result. The tests consisted of pre-test and post-test, which were conducted before and after each cycle. This class consisted of 28 students. Each cycle consisted of four steps: planning, action, observation and reflection. The data were collected from field notes and interview result. The tests consisted of pre-test and post-test, which were conducted before and after each cycle. The research analyzed the average score of each test to find out the improvements of students “reading comprehension in narrative texts after the action was conducted. The result of the research showeds that there was improvement of students’ reading comprehension after they were taught through picture series. There was an improvement on the students “average score of the text. It can be concluded that the teacher choose picture-series as the media facilitates the students’ to improve their comprehension in reading narrative text.